The Celluloid Specimen Moving Image Research into Animal Life - Schultz-Figueroa, Benjamin (University of California Press, 2023)
In The Celluloid Specimen, Benjamín Schultz‑Figueroa examines rarely seen behaviorist films of animal experiments from the 1930s and 1940s. These laboratory recordings-including Robert Yerkes's work with North American primate colonies, Yale University's rat‑based simulations of human society, and B. F. Skinner's promotions for pigeon‑guided missiles-have long been considered passive records of scientific research. In Schultz‑Figueroa's incisive analysis, however, they are revealed to be rich historical, political, and aesthetic texts that played a crucial role in American scientific and cultural history-and remain foundational to contemporary conceptions of species, race, identity, and society. "Essential reading for anyone in behavioral science and media studies." - LISA CARTWRIGHT, University of California, San Diego "Remarkable and urgently needed. Benjamín Schultz‑Figueroa disinters an extraordinary lost archive that sheds new light on race, eugenics, species, the science of sex, and biopolitics. A resonant- and stunningly clear-intervention." - DONOVAN SCHAEFER, author of Wild Experiment: Feeling Science and Secularism after Darwin "A fertile, sprawling, kaleidoscopic work. No book outlines the multiple functions of the scientific moving image as thoroughly. A brilliant and essential addition to animal studies, cinema and media studies, and the history of science." - SCOTT CURTIS, author of The Shape of Spectatorship: Art, Science, and Early Cinema in Germany "Seriously speculative, meticulously researched, and boldly interdisciplinary, The Celluloid Specimen cross‑pollinates nontheatrical film studies and critical animal studies with stunning acumen and gripping analysis." - YIMAN WANG, University of California, Santa Cruz